Impact of endurance training on mitochondrial H2O2 production and NRF2 levels in different rat organs - Galganski, Lukasz; Wojcicki, Krzysztof; Jarmuszkiewicz, Wieslawa; Zoladz, Jerzy A. (Frontiers in Molecular Biosciences, 2025)
BackgroundIn recent years, increasing attention has focused on the effect of exercise on redox balance and the expression of nuclear factor erythroid 2-related factor 2 (NRF2), widely recognized as the master regulator of antioxidant defense mechanisms. However, surprisingly little is known about how physical training influences H2O2 production and NRF2 expression across various vital organs.MethodsWe investigated the effects of endurance training on the oxidative capacity, reactive oxygen species production, and antioxidant defense of various body organs in rats. Sixteen 4-month-old male Wistar rats were randomly assigned to either an endurance training group (8 weeks of treadmill running, n = 8) or a sedentary control group (n = 8).ResultsIn the endurance training group, maximal oxidative activity increased in all examined tissues (lung, brain, liver, and hind limb skeletal muscle) except the heart. Under phosphorylating conditions, H2O2 production remained unchanged in all tissues except the heart, where it increased. Under non-phosphorylating conditions, H2O2 production increased only in the liver and heart. In all tissues, H2O2 production was consistently lower under phosphorylating than non-phosphorylating conditions. The level of malondialdehyde, a marker of oxidative damage, did not increase in the examined tissues, except the lungs, where it even decreased. Superoxide dismutase 1 levels increased in the lung, brain, and skeletal muscle, but decreased in the heart and remained unchanged in the liver. NRF2 protein levels were significantly elevated in all examined tissues, accompanied by an increase in glutathione reductase levels.ConclusionGiven the cytoprotective capacity of NRF2, we postulate that the NRF2-regulated adaptive multi-organ response may play a key role in the widely described beneficial effects of physical activity on various body organs and body health.